2013
DOI: 10.1111/brv.12066
|View full text |Cite
|
Sign up to set email alerts
|

How insects overcome two‐component plant chemical defence: plant β‐glucosidases as the main target for herbivore adaptation

Abstract: Insect herbivory is often restricted by glucosylated plant chemical defence compounds that are activated by plant β-glucosidases to release toxic aglucones upon plant tissue damage. Such two-component plant defences are widespread in the plant kingdom and examples of these classes of compounds are alkaloid, benzoxazinoid, cyanogenic and iridoid glucosides as well as glucosinolates and salicinoids. Conversely, many insects have evolved a diversity of counteradaptations to overcome this type of constitutive chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 172 publications
(322 reference statements)
3
150
0
2
Order By: Relevance
“…It is widely accepted that the digestive activation of salicinoids leads to toxic products warding off non-adapted herbivores. For salicortin, it has been proposed that activation proceeds through deglucosylation by β-glucosidases (Clausen et al 1990;Lindroth 1988;Pentzold et al 2014). The aglycon is either hydrolyzed spontaneously in the alkaline gut environment or degraded enzymatically by insect esterases Lindroth 1989) to saligenin and a 1-hydroxy-6-oxocyclohex-2-en-1-oyl (HCH) fragment (Haruta et al 2001;Julkunen-Tiitto and Meier 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that the digestive activation of salicinoids leads to toxic products warding off non-adapted herbivores. For salicortin, it has been proposed that activation proceeds through deglucosylation by β-glucosidases (Clausen et al 1990;Lindroth 1988;Pentzold et al 2014). The aglycon is either hydrolyzed spontaneously in the alkaline gut environment or degraded enzymatically by insect esterases Lindroth 1989) to saligenin and a 1-hydroxy-6-oxocyclohex-2-en-1-oyl (HCH) fragment (Haruta et al 2001;Julkunen-Tiitto and Meier 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the salicinoid breakdown follows reported routes like deglucosylation, ester cleavage and conjugation (Clausen et al 1990;Lindroth 1988;Pentzold et al 2014). The structural diversity of the compounds -namely, the differential substitution of quinic acid with salicylate or benzoate -can be rationalized by acyl migration under basic conditions as present in the insect gut (Appel and Martin 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the activity of this enzyme is often used as a biochemical indicator in research on plant metabolic status under different experimental situations. Pentzold et al (2013) reported that insect herbivory is often restricted by glucosylated plant chemical defense compounds that are activated by plant b-glucosidases to release toxic aglycones upon plant tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Pea (Pisum sativum L.) (Fabaceae), originally a plant of the Near East and one of the most ancient crops dating back to the end of the last Ice Age in Europe, is currently grown all over the world in temperate regions, at low and high elevations or during cool seasons in warm regions (Ljuština and Mikić 2010;Pavek 2012). Pea is cultivated basically in pure stands as a commercial crop but it is also used as a forage, rotational, and cover crop or green manure.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes that catalyze such reactions often belong to the glycosyl hydrolase family 1 (GH1) according to CAZy [96,97]. Whereas in plants, GH1s play an important role in the activation of glucosides for defense purpose [98][99][100][101], insects use those enzymes mainly for digestion, either in the gut or in the salivary glands [24,102,103]. In addition to this, GH1s may also be involved in the production of chemical defenses widely distributed in insects [104].…”
Section: Iridoid De Novo Synthesis: Late Stepsmentioning
confidence: 99%